Association of preoperative ultrasonographic parameters of the contralateral kidney with long-term serum creatinine in cats treated for unilateral ureteral obstruction - Pulido Vega, Diego; Ficheroulle, Jérémie; Manassero, Mathieu; Mortier, Jeremy; Maurey, Christelle (Frontiers in Veterinary Science, 2025)
IntroductionPrediction of renal recovery after surgical management of feline unilateral ureteral obstruction (UO) is crucial to guide therapeutic decisions, but predictors of this outcome are still lacking. Despite the functional importance of the contralateral kidney, there is currently no precise description of its ultrasonographic (US) features. In addition, US parameters of both the renal collecting system and the renal parenchyma have been identified in human medicine as prognostic factors in the case of UO but have not been described in veterinary medicine. The aim of this study was to evaluate an association between preoperative structural US renal parameters and long-term International Renal Interest Society (IRIS) stage after successful renal decompression with subcutaneous ureteral bypass (SUB) device in cats with unilateral UO.MethodsThis retrospective study included 60 cats with unilateral UO and evaluated preoperative US parameters of both kidneys, including measurements of parenchymal and pelvic areas as well as a renal score. Cats were divided according to their serum creatinine at 3 months postoperatively into group A (IRIS stages I and II) and group B (IRIS stages III and IV).ResultsA higher US chronic kidney disease (US-CKD) score of the kidney contralateral to the UO was associated with long-term IRIS stages III and IV. It also appeared as a fair discriminator of long-term IRIS stage IV, with an area under the curve of 0.74. The optimal cutoff value for accurately identifying cats with long-term IRIS stage IV was a US-CKD score > 7, with a specificity of 98%, a sensitivity of 25%, and a positive likelihood ratio of 12.75. No preoperative US parameters regarding the obstructed kidney, including parenchymal and pelvic areas, were significantly associated with long-term creatinine.ConclusionUltrasonographic scoring of contralateral chronic kidney disease abnormalities is associated with IRIS stage following treatment of feline unilateral UO with a SUB device and serves as a specific indicator of cats presenting with long-term IRIS stage IV.